The Penaeus stylirostris densovirus capsid protein interacts with the Litopenaeus vannamei BCCIP protein. Issue 88 (May 2019) - Zeng, Digang; Peng, Min; Yang, Qiong; Yang, Chunling; Liao, Zhenping; Li, Qiangyong; Liu, Qingyun; Zhu, Weilin; Wang, Hui; Li, Min; Chen, Xiaohan; Xie, Daxiang; et al.
Abstract: Viral capsid proteins play an important role in the viral infection process. To identify the cellular proteins in shrimp that interact with the Penaeus stylirostris densovirus capsid protein (PstDNV-CP), we constructed a yeast two-hybrid (Y2H) cDNA library of the muscle tissue of Litopenaeus vannamei, and hybridized the bait vector pGBKT7-CP with this library. Cloning and sequencing showed that the shrimp protein interacting with PstDNV-CP was a homolog of BRCA2 and CDKN1A(p21)-interacting protein (BCCIP). We named this protein L. vannamei BCCIP (LvBCCIP). Further analysis showed that LvBCCIP interacted with L. vannamei calmodulin (LvCaM). We validated the interactions between PstDNV-CP and LvBCCIP, and between LvBCCIP and LvCaM, with GST pulldown assays. The gene expression of LvBCCIP increased significantly after PstDNV challenge. In addition, the PstDNV titer of PstDNV-challenged shrimp was significantly reduced after LvBCCIP expression was inhibited using double-stranded RNA (dsRNA) interference. These results indicated that LvBCCIP is critical to PstDNV pathogenesis in L. vannamei . Interestingly, the growth rate of L. vannamei was significantly reduced when LvBCCIP gene expression was silenced, indicating that LvBCCIP may also be associated with growth regulation in L. vannamei . Thus, the interaction between PstDNV-CP and LvBCCIP might explain why PstDNV infection leads to runt-deformity syndrome in shrimp. Highlights: The L. vannamei BCCIP protein interacted with PsDNV-CP. The L. vannamei calmodulin protein also interacted with BCCIP. When L. vannamei BCCIP gene expression was silenced, PsDNV proliferation was reduced and shrimp growth decreased. The interaction between PstDNV-CP and LvBCCIP might explain why PstDNV infection leads to RDS in shrimp.